Evaluation of pediatric hydroxyurea prescriptions for patients with sickle cell disease - Fernanda Alice Tanimoto Duque; Elaine Ferreira Dias; Jéssica Soares Malta; Priscila Cezarino Rodrigues; Lucas de Faria Martins Braga; Josiane Moreira da Costa (O Mundo da Saúde, 2022)
Hydroxyurea (HU) was one of the main advances in the treatment of sickle cell disease. The use of the drug in children in Brazil is still off-label and is only available in solid pharmaceutical form. The objective of the present study is to evaluate the strategies for adapting the solid dosage form for use in children with sickle cell disease. This is a descriptive study, with the analysis of pediatric HU prescriptions and the application of questionnaires to those responsible in the period from January to March 2018. 43 prescriptions were analyzed, and two forms of adaptation were identified, 1) conventional dilution: dilution of the drug in a pre-prescribed quantity - determined amount of water, followed by administration of part of the solution obtained (22) (51%), and 2) use of the holiday or intermittent dose recommendation (21) (49%). All patients using the conventional dilution strategy discarded the remainder of the drug from the domestic sewage system. In addition, incorrect administration of the drug was identified in one patient. The lack of an appropriate pharmaceutical form for the pediatric population can lead to risks of incorrect administration and unnecessary expenses with drug disposal, in addition to improper disposal that compromises environmental factors. This study reinforces the need to develop pharmaceutical forms that are more suitable for children.